2005
DOI: 10.1073/pnas.0500770102
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic evolution of MHC class I region in primates

Abstract: To elucidate the origins of the MHC-B-MHC-C pair and the MHC class I chain-related molecule (MIC)A-MICB pair, we sequenced an MHC class I genomic region of humans, chimpanzees, and rhesus monkeys and analyzed the regions from an evolutionary stand-point, focusing first on LINE sequences that are paralogous within each of the first two species and orthologous between them. Because all the long interspersed nuclear element (LINE) sequences were fragmented and nonfunctional, they were suitable for conducting phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 54 publications
5
62
0
Order By: Relevance
“…Orthologues of HLA-C have been identified in chimpanzees, gorillas, and orangutans (2,24,25), but not in Old World monkeys (1). Hence, the HLA-C locus appears to represent a recent duplication of the HLA-B locus that occurred after the divergence of apes from Old World monkeys (1,8,15). However, rhesus macaques have multiple duplications of the Mamu-A (Macaca mulatta [21]) and Mamu-B loci (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Orthologues of HLA-C have been identified in chimpanzees, gorillas, and orangutans (2,24,25), but not in Old World monkeys (1). Hence, the HLA-C locus appears to represent a recent duplication of the HLA-B locus that occurred after the divergence of apes from Old World monkeys (1,8,15). However, rhesus macaques have multiple duplications of the Mamu-A (Macaca mulatta [21]) and Mamu-B loci (8).…”
mentioning
confidence: 99%
“…Three different SIV smm/mac Nef variants downregulated CD8 chimeras with cytoplasmic tail sequences typical of Mamu-A and -B molecules known to bind SIV CTL epitopes in rhesus macaques but did not downregulate chimeras with the cytoplasmic tails of other Mamu-B or -E molecules. Since Old World monkeys do not have an MHC class I C locus (1,8,15), gene products of one or more of the duplicated B loci may serve as KIR ligands for the inhibition of NK cell responses. Furthermore, given the sequence conservation among MHC class I E alleles of different primate species (7,22), it is likely that rhesus macaque and sooty mangabey MHC class I E molecules serve as ligands for CD94/NKG2 receptors on NK cells (9,10,26,27).…”
mentioning
confidence: 99%
“…Great apes are represented by the chimpanzee, bonobo, gorilla and orangutan; old world monkeys by the rhesus macaque, and the ancestral prosimians by the ring-tailed lemur. Humans shared a common ancestor with the chimpanzee/bonobo, gorilla, and orangutan approximately 6, 8, and 16 MY ago (Chen and Li 2001), and with the rhesus macaque and ring-tailed lemur approximately 27-30 and 55 MY ago, respectively (Goodman 1999;Fukami-Kobayashi et al 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Genetic analysis has revealed that the xMHC, which is still rapidly evolving, arose through block duplications of simpler ancestral patterns, followed by diversification, leading to five subregions, the extended class I, classical class I, classical class III, classical class II, and extended class II. 22,23 We have seen how HERV recombination may create this pattern of block duplications, and, as Dawkins and colleagues demonstrate, the human MHC is densely colonized by HERVs and retroelements, which are likely to have played an important part in its evolution. 24 Villarreal has probed the evolution of adaptive immunity, and the origin of self, to propose a comprehensive hypothesis in which viruses in general, and retroviruses in particular, have played a key role in the evolution of immunity and the recognition of self from the simpler non-adaptive systems of marine invertebrates, to the sudden, almost explosive, origins of true adaptive immunity in jawed fish, with its subsequent refinements, each accompanied by new expansions of retroviruses, with the origins of mammals, and, finally, primates.…”
Section: Hervs In Autoimmune Diseasementioning
confidence: 99%
“…37 Portis, in his review, re-visited the superantigen-in-diabetes controversy, drawing attention to the fact that the HERV-K related sequence found in the pancreatic islets of patients with insulin dependent diabetes mellitus (ID-DMK 12 22) had now been identified as the env gene of HERV-K18, and this had been located to the first intron of the CD48 gene on chromosome 1. Conrad and colleagues had also shown that HERV-K18, which appears to be a solitary insert, coded for three alleles, one of which was ID-DMK 12 22 and the other two were full-length env An alternative approach to medical genetics based on modern evolutionary biology. Part 3: HERVs in diseases genes, all of which encoded superantigens.…”
Section: Type 1 Diabetesmentioning
confidence: 99%